2017
DOI: 10.4038/cjs.v46i2.7434
|View full text |Cite
|
Sign up to set email alerts
|

The effect of iron corrosion in cast iron pipes on the microbiological quality of drinking water: a laboratory and field investigation

Abstract: Iron pipelines are commonly used in old drinking water distribution systems, adding rust to pipe-borne water. Chlorine added to water for disinfection could react with iron that leaches from these iron pipelines, thereby reducing available free chlorine for disinfection. The consumption of dissolved chlorine by iron and consequent effects on the microbiological quality of drinking water were investigated, by spiking Serratia marcescens and Escherichia coli into different known mixtures of Fe 2+ and chlorine. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This may present a risk when silicate is used as a water treatment additive. 4. Orthophosphate promoted biofilm growth, but it did not disrupt the community structure in comparison to the biofilms exposed to silicates.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This may present a risk when silicate is used as a water treatment additive. 4. Orthophosphate promoted biofilm growth, but it did not disrupt the community structure in comparison to the biofilms exposed to silicates.…”
Section: Discussionmentioning
confidence: 93%
“…1,2 Corrosion by-products can react with disinfectant, neutralizing it before it can inactivate microorganisms in the bulk water or biofilm. 1,3,4 To mitigate corrosion, drinking water treatment plants apply corrosion inhibitors while making adjustments to pH and alkalinity. According to a 2019 corrosion control survey, 54% of utilities in the US utilize a phosphate-based corrosion inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of this excessively thick, rough corrosion scale explains the reduction in corrosion rate over time, but it is detrimental for water systems because it obstructs the flow passage of the pipes. Furthermore, these conditions might increase the risk of bacteria proliferation, because it has been demonstrated that they cause a consumption of disinfectant [5,26].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the identification of Fe 2 + and Cu 2 + ions, considered as heavy metal ions, is vital due to their existence in wastewater originated from the various industrial plants. [19][20][21] The taste, colour and aroma of water are generally influenced by the presence of surplus iron in water. Excess intake of iron containing water poses harmful consequences such as liver cancer, diabetes, alzheimer's disease, and other diseases.…”
Section: Introductionmentioning
confidence: 99%